Influence of freezing on changes in the structure of black currant fruits - Osokina, Nina; Kostetska, Kateryna; Herasymchuk, Olena; Tkachenko, Hennadii; Podpriatov, Hryhorii; Pusik, Ludmila; Falendysh, Natalia; Bobel (Zinchenko), Inna; Belinska, Kristina (My University, 2021)
Investigated problem was substantiation of the influence of the method, the duration of freezing on changes in the structure of black currant fruits of different degrees of maturity and pomological varieties. The main scientific results: the advantages of fast freezing of black currant fruits in a fast freezing chamber with forced air circulation at a speed of 1.5–2.5 m/s at a temperature of -30 …- 32 °C compared to slow freezing in " Calex " freezers were established at a temperature of -20 …- 22 °C. Rapid freezing forces cooling, freezing and freezing due to a decrease in the temperature of initiation of ice formation, an increase in the rate of heat extraction and an increase in the temperature of freezing. Досліджувана проблема - обґрунтування впливу способу, тривалості заморожування на зміну структури плодів чорної смородини різного ступеня зрілості та помологічних сортів. Основні наукові результати: встановлено переваги швидкого заморожування плодів чорної смородини в камері швидкого заморожування з примусовою циркуляцією повітря зі швидкістю 1,5-2,5 м/с за температури -30...- 32 °С порівняно з повільним заморожуванням у морозильних камерах «Calex» за температури -20...- 22 °С. Швидке заморожування прискорює охолодження, підморожування і заморожування за рахунок зниження температури початку льодоутворення, збільшення швидкості відбору тепла і підвищення температури заморожування.
Keywords: freezing; fresh fruits; frozen fruits; плоди чорної смородини; заморожування; свіжі фрукти; ягоди; технології хлібопекарських і кондитерських виробів